2021
DOI: 10.17533/udea.redin.20211063
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic treatment based on TiO2 for a coal mining drainage

Abstract: The aim of the present work was to evaluate the effectiveness of a heterogeneous photocatalyst based on TiO2 in the treatment of coal mining drainage which contains a variety of heavy metals and high concentration sulfates and sulfides. The photocatalytic behavior of the commercial reference Sigma Aldrich and the different materials synthesized using the Sol-gel methodology with surface modifications using sulfation and fluorination processes were analyzed. To find a possible correlation between the physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The main signal for T iO 2 is observed around 2θ = 25.25°, which indicates the presence of only the Anatase crystalline phase for this material [4,16]. In the case of N b 2 O 5 , the main signal can be observed around 2θ = 28.58°due to the plane (100), corresponding to the crystalline N b 2 O 5 in the hexagonal phase [13,16].…”
Section: Characterization Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The main signal for T iO 2 is observed around 2θ = 25.25°, which indicates the presence of only the Anatase crystalline phase for this material [4,16]. In the case of N b 2 O 5 , the main signal can be observed around 2θ = 28.58°due to the plane (100), corresponding to the crystalline N b 2 O 5 in the hexagonal phase [13,16].…”
Section: Characterization Resultsmentioning
confidence: 84%
“…It has also been reported that the heterojunction formation between mixed oxides such as ZnO, T iO 2 , and N b 2 O 5 is an effective way to achieve a better separation of photogenerated charges. This improves the photocatalytic response of these materials [13], and therefore, the effectiveness of the composed materials in wastewater treatment by photocatalytic processes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%